OCTOBER OF 1917: ATTITUDE OF THE LEADERS OF THE SOVIET STATE TO THE REVOLUTION, TO THE CULTURE AND TO THE ART - E. V. Zhbankova (Концепт: философия, религия, культура, 2017)
State policy in the sphere of culture is developed under the influence of governors’ views. In the post-revolutionary period it depended on the views of L. Trotsky, A. Bogdanov, A. Lunacharsky. These people were not laymen in the sphere of culture. Long before the revolution they published their numerous articles and formed their opinion about the art development. When they held the highest leadership positions in the State, they influenced greatly the official policy in the sphere of art. Their views were not identical and sometimes even contradicted with each other. Before the revolution each of them had elaborated their conceptions of social life having taken into account the specifics of the Russian culture. The common idea in their diverse views was the socio-materialistic class approach to the analysis of complicated processes of social development and justification of the thesis about the necessity of revolutionary changes in the sphere of art on the basis of transition to the higher stage of social life. In the post-revolutionary years many of these philosophical conceptions were specified in accordance with the altered conditions and were united into one common conception which was supplemented with the practical political program of cultural development. The program also included the system of state measures for the formation and development of a new form of art, namely the proletarian culture.